2005
DOI: 10.1074/jbc.m509646200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3,4,5-Trisphosphate Mediates Aldosterone Stimulation of Epithelial Sodium Channel (ENaC) and Interacts with γ-ENaC

Abstract: Whole cell voltage clamp experiments were performed in a mouse cortical collecting duct principal cell line using patch pipettes back-filled with a solution containing phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ). PIP 3 significantly increased amiloridesensitive current in control cells but not in the cells prestimulated by aldosterone. Additionally, aldosterone stimulated amiloridesensitive current in control cells, but not in the cells that expressed a PIP 3 -binding protein (Grp1-PH), which sequestered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 45 publications
3
55
2
Order By: Relevance
“…Although it is clear that glucocorticoid hormones do induce SGK1 expression (31), SGK1 is an important downstream target of PI3K (29), and data from several absorptive cell types have suggested that insulin can increase the apical abundance of ENaC via a mechanism dependent on a PI3K-mediated increase in SGK1 activity (2,8,46,51). Moreover, PIP 2 and PIP 3 also activate ENaC by binding to the channel complex, and this provides another mechanism by which PI3K-coupled agonists, such as insulin, can stimulate Na ϩ transport (20,42,43,52). However, although the present data show that insulin stimulation/PI3K-P110␣ expression can control G Cl , these maneuvers had no effect on G Na in hormonedeprived cells but augmented the dexamethasone/SGK1-induced G Na .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is clear that glucocorticoid hormones do induce SGK1 expression (31), SGK1 is an important downstream target of PI3K (29), and data from several absorptive cell types have suggested that insulin can increase the apical abundance of ENaC via a mechanism dependent on a PI3K-mediated increase in SGK1 activity (2,8,46,51). Moreover, PIP 2 and PIP 3 also activate ENaC by binding to the channel complex, and this provides another mechanism by which PI3K-coupled agonists, such as insulin, can stimulate Na ϩ transport (20,42,43,52). However, although the present data show that insulin stimulation/PI3K-P110␣ expression can control G Cl , these maneuvers had no effect on G Na in hormonedeprived cells but augmented the dexamethasone/SGK1-induced G Na .…”
Section: Discussionmentioning
confidence: 99%
“…These anionic phospholipids control many aspects of cell physiology by activating PI3K and downstream kinases such as SGK1 (15,29) and by directly controlling ion channel activity (see, for example, Refs. 20,22). Since PI3K has also been reported to control G Cl in arterial smooth muscle (13), subsequent experiments explored the effects of artificially increasing cellular PI3K activity by transiently expressing membraneanchored PI3K-P110␣ (see Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Briefly, the mpkCCD c14 cells were incubated in a 1:1 mix of DMEM:F12 medium (Invitrogen, Carlsbad, CA) supplemented with 50 nM dexamethasone, 1 nM triiodothyronine, 20 mM Hepes, 2 mM L-glutamine, 0.1% penicillin/ streptomycin, and 2% heat-inactivated FBS. Cells were maintained at 37°C with 5% CO 2 in air for 2 weeks until they formed a confluent monolayer and became fully polarized.…”
Section: Concise Methodsmentioning
confidence: 99%
“…Phosphatidylinositide 3-OH kinase (PI3-K) is central to many cellular signaling pathways that control ENaC activity (8 -10). In particular, PI3-K is an effector that is necessary for aldosterone and insulin control of the channel (11)(12)(13)(14)(15). Both aldosterone and insulin stimulate PI3-K signaling and increase the levels of the phosphoinositide products of this kinase in renal epithelial cells (13,16).…”
mentioning
confidence: 99%